Violation of the Statement Structure as a Communicative Failure (Proceedings of Southern Federal University. Philology, 2020)
Among the many barriers that impede the process of communication in a foreign language, we are particularly interested in those that impede the further development of the communication process, and sometimes make it practically impossible. Such barriers are called communicative failures, and the methodologist’s task is to develop a technology for identifying them in accordance with a specific criterion. The article specifies the success criterion of a communicative act. In the case of a productive speech act, communicative failures are often associated with the communicator’s improper planning of his/her speech behavior in the initial period of verbalization, in particular, the wrong choice of design, when the communicative and objective goals of the speech act do not correspond to the specific situational context within which this communicative act unfolds.By communicative failure it is understood such a failure in communication when the communicative act does not fulfill its function. The task is analyzed, which involves filling out the questionnaire in the non-native language of the respondent, requiring fairly short and unambiguous answers. However, in some cases, as a result of the substitution of basic information with secondary (specifying) answers, they could be interpreted differently and, therefore, applied to various communicative situations. The following conclusion is made: a speech act, correlated with more than one context, provides a greater degree of freedom for the interpretation of its purpose and, therefore, allows various ways of reacting to its content. It is such an act that can be attributed to unsuccessful.Key words: speech act, communicative failure, context, questionnaire, interpretation.DOI 10.18522/1995-0640-2020-2-71-77